2011
DOI: 10.1254/jphs.10302fp
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Dexamethasone on Hepatocyte Growth Factor–Induced DNA Synthesis and Proliferation in Primary Cultures of Adult Rat Hepatocytes

Abstract: Abstract. We investigated the effects of dexamethasone on hepatocyte growth factor (HGF)-induced DNA synthesis and proliferation in serum-free primary cultures of adult rat hepatocytes. Isolated hepatocytes were cultured at a density of 3.3 × 10 4 cells/cm 2 in Williams' medium E containing 5% newborn bovine serum and various concentrations of dexamethasone for 1, 2, and 3 h. After a 3-h attachment period, the medium was then changed, and cells were cultured in serumfree dexamethasone (10 −10 M)-containing Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…High doses of glucocorticoids, especially dexamethasone, suppress the expression of hepatocyte growth factor due to declined proliferation capacity. The liver cell morphological alterations were associated with sinusoid plus central vein dilatation [27]. Dexamethasone elevated the Fig.…”
Section: Discussionmentioning
confidence: 95%
“…High doses of glucocorticoids, especially dexamethasone, suppress the expression of hepatocyte growth factor due to declined proliferation capacity. The liver cell morphological alterations were associated with sinusoid plus central vein dilatation [27]. Dexamethasone elevated the Fig.…”
Section: Discussionmentioning
confidence: 95%
“…hHGF was originally separated and purified from serum of a patient with severe hepatitis, and it represents one of the most well-studied factors that is important for hepatocyte regeneration. Because of its ability to promote hepatocyte division and proliferation in vitro [31,32], hHGF treatment has quickly become widespread. Clinical hHGF is a small molecule (peptide) that is extracted from suckling pigs or fetal bovine livers.…”
Section: Discussionmentioning
confidence: 99%
“…hHGF treatment has been found to promote hepatocyte mitosis and play a significant role in prevention and treatment of acute and chronic liver injury [33]. The predominant biological activities of hHGF consist of the following: stimulating DNA synthesis in hepatocytes and promoting hepatocyte mitosis and proliferation, thus rapidly repairing damaged liver tissues [31,32]; reducing lipid peroxide levels during acute hepatic necrosis by inhibiting TNF-a release, stabilizing cell and mitochondrial membranes of hepatocytes, and mitigating hepatocyte necrosis [34]; decreasing bilirubin and hyaluronic acid content; promoting oxidative phosphorylation and activating oxidation-related functions and protein synthesis in hepatocytes; and protecting against hepatocyte injury [35]. Recent studies have shown that hHGF can also prevent hepatocyte apoptosis, alleviate liver fibrosis, and improve hepatic microcirculation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The viability of hepatocytes consistently exceeded 96%, as determined by trypan blue exclusion assay. Unless otherwise indicated, isolated hepatocytes were plated onto 6-well collagen-coated plastic culture dishes (35 mm diameter; Iwaki Glass Co., Tokyo, Japan) at a density of 3.3  10 4 cells/cm 2 in minimum essential medium containing 5% bovine calf serum and 10 -10 M dexamethasone for 3 h in 5% CO 2 in air (Kimura et al, 2011). The medium was then changed, and cells were cultured in serum-free minimum essential medium containing various concentrations of L-ascorbic acid with or without adrenergic agonists or specific inhibitors of signal transducers.…”
Section: Hepatocyte Isolation and Culturementioning
confidence: 99%